The Incidence of Acute Respiratory Infection (ARI) in Toddler in Mandosawu Village Poco Ranaka Sub-District East Manggarai Regency - Dorce, Maria Kolumba; Setyobudi, Agus; Salmun, Johny A. R (Timorese Journal of Public Health, 2021)
Acute respiratory infection (ARI) is an acute respiratory tract infection that attacks one or more parts of the respiratory tract. ARI in toddlers can be caused by 2 factors, namely intrinsic and extrinsic factors. The data on ARI cases at the Mano Health Center in 2019 was 1338 cases and in 2020 it was 1564 cases. This study aims to determine the factors associated with the incidence of ARI in Mandosawu Village in 2020. This type of research is a quantitative study with a case control study approach. The population in this study were all children under five who were in Mandosawu Village, Poco Ranaka District, East Manggarai Regency, this study was conducted from December to February, while the sample was 106 toddlers with 53 case samples and 53 control samples and the population in this study was 2709 taken by simple random sampling. The results showed that the factors associated with the incidence of ARI were ventilation conditions (p=0.000, OR=4.926; 95% CI: 2.159-11.239), wall type (p=0.000, OR-6.750, 95% CI: 2.854-15.962) , type of floor (p=0.000, OR-8.656; 95% CI: 3.597-20.827), occupancy density (p=0.037, OR=2.425; 95% CI: 1.403-5.390), smoking habits of family members (p=0.000, OR = 4.180; 95% CI: 1.489-9.452), while the factors that have no relationship with the incidence of ARI are the use of cooking fuel (p = 0.066) and the mother's habit of bringing toddlers when cooking (p = 0.69). There is a relationship between the type of ventilation, the type of wall, the type of floor, the density of the dwelling.